ANALYSIS OUTPUT TOLERANCE LIMITS X-RAY MACHINE DIAGNOSTIC (Case Study in one of the General Hospital inBanda Aceh) - Evi Yuvita; Rini Safitri (Universitas Syiah Kuala, 2012)
Currently, several regional general hospitals in Banda Aceh now have excellent support facilities, one of which is a diagnostic X-ray machine. The performance of diagnostic X-ray machine should be checked to determine if the dose received does not harm a patient and produce a good image and provide diagnostic information in a timely and accurate, therefore there are necessary for quality control activities on the machine X-ray. Factors that affect the dosing and imaging results, among others, the amount of the provision of current and voltage. From the research shows that the value of the output voltage generated is not much different from the value of the input voltage with a percentage value below 5%. This value shows a good output machineX-ray because it is still under the maximum tolerance limit of 10%. So the overall results of observations on the machineX-ray is in hospital, the quality control measurements gave values still within safe limits. Then by giving a higher input voltage turns also affect the amount of energy produced, thus affecting also absorbed dose X-rays are produced.